DOES THE SIZE OF A BANK MODERATE THE RELATIONSHIP BETWEEN CKPN, BOPO, AND NPL TOWARD BANK FINANCIAL PERFORMANCE? - Jaya Prasetya Sakti; Nurul Aisyah Rachmawati (Jurnal Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of Allowance for Impairment Losses (AFIL), Operational Expenses (OEOI), and Non-Performing Loans (NPL) on Bank Performance with Company Size as a moderating variable. The population of this research is financial services companies, banking sub-sectors listed on the Indonesia Stock Exchange (IDX) in 2019 and 2022. Based on the purposive sampling method, the number of samples for this research is 35 banks with 140 data observations. The results of the analysis are that banking performance as proxied by return on assets (ROA) will decrease if the AFIL, OEOI and NPL variables increase and the company size as proxied by total assets does not change (fixed), AFIL has a significant negative effect on financial performance, OEOI has a significant negative effect on financial performance, NPL has a significant negative effect on financial performance, Company Size weakens the relationship between AFIL and OEOI on financial performance, and Company Size cannot moderate the relationship between NPL and financial performance.